The Influence of Enterprise Resource Planning (ERP) System on Customer Satisfaction - Zheng, Chengyi; Kim, Seongdok (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2023)
Purpose: This study investigates the influence of Enterprise Resource Planning (ERP) systems on customer satisfaction in small-sized companies in Xinyang City, China. The research aims to identify factors affecting customer satisfaction towards ERP systems and provide suggestions for optimizing the system to improve user experience and overall competitiveness. Four hypotheses are proposed, examining the impact of information quality, system quality, service quality, and perceived usefulness on customer satisfaction. Research design, data and methodology: The research employs a questionnaire survey targeting 393 employees from 100 small companies in Xinyang City, with participants having at least one year of experience using ERP software. Multiple regression analysis is used to test the hypotheses and analyze the data collected from the questionnaires. Results: The results proved that system quality, service quality, and perceived usefulness have a statistically significant positive causal relationship with customer satisfaction while information quality does not have causal relationship. Conclusions: The findings of this study will contribute to understanding the role of ERP systems in enhancing customer satisfaction and provide valuable insights for software developers and small enterprises looking to optimize their ERP implementation.